PENGARUH PERISTIWA POLITIK TERHADAP PERUBAHAN HARGA SAHAM - Fenny Trisnawati (Program Studi Pendidikan Ekonomi Universitas Riau, 2012)
Stock market has a high risk, especially political risk. Investors also invest theirmoney in foreign country. Therefore political condition needs to be considered byinvestor, because it can affect stock price. Research purpose is to acknowledgeeffect of political event (presidential election) on stock price on LQ 45 group atIndonesia Stock Exchange 2004 and 2009. Research type is verificative andresearch method is explanatory survey. Amount of sample used on presidentialelection 2004 event is 31 companies and on presidential election 2009 event are 45companies. Sample technique purposive sampling. Analysis method used iscompare means one sample t test. Result of this research indicates there`s nodifferent between average abnormal return before and after Republic Indonesiapresidential election event in 2004, but there`s a different between averageabnormal return before and after Republic Indonesia presidential election event in2009. This indicates that Republic Indonesia presidential election event does notimply the market (investor) reaction and not uses by investor as a based on decisionmaking to buy or sell shares.